Трифенiлфосфiноксид iнгiбiтор для захисту залiза вiд корозiї у кислих середовищах - Присяжний, В.Д.; Вишневська, Ю.П.; Родiонов, В.Н.; Ткаленко, Д.А.; Бик, М.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Inhibitive influence of triphenylphosphineoxide (Ph)3P=O on iron corrosion in acid solutions is found. Inhibitive effect shows up in the deceleration of both anode and cathode processes. It is assumed that its appearance is related to the formation of a surface layer of slightly dissolutive complex compounds which appear as a result of the reaction of triphenylphosphineoxide with cations of the dissolving metal.